The Role Of Profitability In The Formation Of Dividend Policy - Rizal Fahmi Syaiful; Dede Sri Rahayu; Nadya Ayu Lestari; Nadia Ulfa Agustin Hilman; Galih Nugraha (Jurnal Ilmiah Multidisiplin, 2025)
This research aimed to determine and provide empirical evidence whether there is an influence of of profitability on dividend policy.  The population in this research was 78 financial data obtained from 26 companies that had been included in the High Dividend 20 Index for the period 2019-2021. In sampling, the technique was used purposive sampling.  The sample used in this research was based on the following criteria: companies that had been included in the High Dividend 20 Index  for the period 2019-2021, companies that had been included in the High Dividend 20 Index  for three consecutive years, companies that distributed their financial statements regularly during the period 2019-2021.  The sample used in this research was 63 financial data from 21 companies with 3 research periods. The method used in this research was verificative analysis. The data analysis technique in this research used panel data regression analysis. Based on the results of hypothesis testing, the profitability ratio had a positive effect on dividend policy.